2014
DOI: 10.4276/030802214x14071472109879
|View full text |Cite
|
Sign up to set email alerts
|

The Human Occupational Impact of Partner and Close Family Caregiving in Dementia: A Meta-Synthesis of the Qualitative Research, Using a Bespoke Quality Appraisal Tool

Abstract: Family dementia caregiving, human occupation, qualitative meta-synthesis.Introduction: In 2009, the United Kingdom Department of Health identified the need to assist families so that people with dementia can remain living at home. Occupational therapists could support families and their loved ones at home by understanding the human occupational impact of caregiving. This impact includes how one is influenced by values and motivated to perform activities shaped by experiences and life roles. The purpose of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
2
8
0
Order By: Relevance
“…It is encouraging to note, however, that qualitative meta-syntheses of the impact of informal caregiving across conditions are beginning to be published. For example, Yong and Price (2014) have recently conducted a comprehensive meta-synthesis of qualitative studies on family caregiving in dementia exploring the occupational impact of dementia caregiving on carers. Although we cannot directly compare their findings to our own (as our review is focused specifically on MS and explored the impact of caregiving from a multidimensional perspective) we consider reviews such as Yong & Price's important for adding to our holistic understanding of the impact of caregiving and the multitude of ways this role can impact on the carer.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…It is encouraging to note, however, that qualitative meta-syntheses of the impact of informal caregiving across conditions are beginning to be published. For example, Yong and Price (2014) have recently conducted a comprehensive meta-synthesis of qualitative studies on family caregiving in dementia exploring the occupational impact of dementia caregiving on carers. Although we cannot directly compare their findings to our own (as our review is focused specifically on MS and explored the impact of caregiving from a multidimensional perspective) we consider reviews such as Yong & Price's important for adding to our holistic understanding of the impact of caregiving and the multitude of ways this role can impact on the carer.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…These were interventions that could be carried out by any professional group. This is corroborated by two further reviews (Hooper and Collins, 2016; Yong and Price, 2014), both of which suggested that occupational therapists could offer interventions to achieve better outcomes for family caregivers and their loved ones.…”
Section: Literature Reviewmentioning
confidence: 70%
“…The UK Prime Minister’s ‘Challenge on Dementia 2020’ (Department of Health UK (DoH), 2015) called for people with dementia and their caregivers to be supported as long as possible in the community before entering formal care. It is acknowledged, however, that each family or partner journey is unique and individuals will experience considerable challenges and constant adaptation throughout the illness trajectory (Yong and Price, 2014). It is therefore important to understand the family caregiver perspective as the intense demands or burden of caring can affect the quality of care and increase the likelihood of the person with dementia entering into formal care (Hall and Skelton, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…A data extraction template was developed in order to support the thematic nature of the review. Thematic reviews use a conceptual framework to provide a lens through which to explore the literature (Yong & Price, 2014) and within the present review, the conceptual framework of occupation as a dynamic synthesis of doing–being–becoming–belonging (Wilcock, 1998; and also Rebeiro et al., 2001) was chosen to frame the analysis. The benefits of using this framework are twofold: providing a novel approach to exploring the occupational experience of dementia caregivers, and establishing whether this is a credible framework for this purpose (Noyes & Lewin, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…This may result in decreased participation in meaningful occupations, threats to wellbeing and loss of occupational balance (Hwang, Rivas, Fremming, Rivas, & Crane, 2009). Systematic reviews of multi-disciplinary literature within an occupational therapy framework have additionally demonstrated that the notions of perceived responsibility and occupational adaptation are key factors in determining the wellbeing of caregivers (Thinnes & Padilla, 2011; Yong & Price, 2014).…”
Section: Introductionmentioning
confidence: 99%